(untitled) (ACME, 2020)
The purpose of this article is to highlight a section of Hegel’s aesthetics that is generally not very thorough, namely the conception of architecture within the system of arts. The aim of the paper is to show how the development of architecture, both in a historical and in a strictly artistic sense, can be a way to focus on some structural tensions of Hegel’s aesthetics. Architecture, precisely because of its status as a work straddling residential functionality and artistic character, is able to highlight the structural aspects of Hegel’s theory of the work of art. First, I will present the essential features of the system of arts in Hegel; second, I will analyze the role of architecture within this system; third, I will focus on a specific architectural form, namely the Gothic cathedral, to outline the specificity of architecture as the art of modernity.